Development of an index that predicts escalation of therapy at an outpatient appointment in patients with known ulcerative colitis (UC) - Walsh, A; Seeva, P; Hinds, C; Sexton, V; Wilson, J; Brain, O; Keshav, S; Uhlig, H; Geddes, JR; Goodwin, GM; Peters, M; Collins, G; et al. (Oxford University Press, 2018)
Conventional follow-up for UC places demands on health services. Demand might be better managed by targeting appointments to those patients who need therapeutic decisions. The aim was to develop a model that would predict the likelihood of escalation of therapy at an appointment.